Diabetes Self-Care Management Among the Elderly in Rural Areas - Vitaliati, Trisna; Irwina Angelia Silvanasari; Nurul Maurida; Achmad Ali Basri (Institut Citra Internasional, 2025)
Diabetes mellitus is susceptible to being experienced by the elderly because of physiological changes caused by the aging process. Diabetes mellitus will accompany the sufferer for life, so the elderly must be able to carry out diabetes self-care management to optimize metabolic control and prevent diabetes complications. In implementing diabetes self-care, this management will certainly be influenced by the characteristics of the sufferer. This study aims to explore the characteristics of elderly with diabetes mellitus in managing their diabetes self-care management in rural areas. The quantitative descriptive research method, with a cross-sectional approach, was carried out among 100 elderly with diabetes mellitus utilizing the purposive sampling method. This research instrument uses The Summary of Diabetes Mellitus Activities. Univariate analysis was performed using frequency distribution. The results of this study show that 57% of the elderly in rural areas had poor diabetes self-care management. Ususally related to the characteristics of the elderly with diabetes mellitus which can influence treatment in managing the disease.This study concludes that there are still elderly people who do not carry out diabetes self-care management independently in their daily lives. This research emphasizes the need for knowledge and awareness to be provided in rural areas regarding Diabetes self-care management. Structured programs need to be designed to improve the behavior of the elderly to promote better adherence to diet, exercise, medication adherence, and proper foot care.